The Role of Cross-Functional Collaboration in Enhancing Data-Driven Branding Strategies in FMCG at Colgate Palmolive India Limited - Mehta, Archie Rajesh (ATLAS SkillTech University, 2025)
The internship report titled "The Role of Cross-Functional Collaboration in Enhancing Data-Driven Branding Strategies in FMCG" provides a comprehensive overview of my enriching experience as a Branding and Analytics Intern at Colgate-Palmolive, a leading FMCG company. The report encapsulates the valuable insights and practical knowledge gained during this internship program, which was undertaken during the summer as part of my second-year MBA curriculum at Atlas Skilltech University. Throughout the internship, I actively participated in various aspects of branding and marketing, including strategizing, consumer research, data analysis, campaign execution, and performance tracking. Under the guidance of Dr. Sashikant Patil, my esteemed faculty mentor, I navigated the dynamic world of FMCG branding and harnessed the opportunity to bridge the gap between theoretical concepts and real-world applications. The report elaborates on the significance of this hands-on experience, highlighting its impact on my professional growth and aligning my academic knowledge with the demands of the modern business landscape. This executive summary aims to provide a glimpse into the detailed findings and reflections shared in the subsequent sections of the report, enabling readers to comprehend the value of this transformative internship experience at Colgate-Palmolive India Limited.
Project Report on The Role of Cross-Functional Collaboration in Enhancing Data-Driven Branding Strategies in FMCG at Colgate Palmolive India Limited (2023-2025) Under the Guidance of Prof. Shashikant Patil
Keywords: Cross-Functional Collaboration; Branding; Branding Strategies; FMCG; marketing